2014
DOI: 10.3389/fgene.2014.00164
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA-dependent transcriptional regulation in neuronal development and disease

Abstract: Comprehensive analysis of the mammalian transcriptome has revealed that long non-coding RNAs (lncRNAs) may make up a large fraction of cellular transcripts. Recent years have seen a surge of studies aimed at functionally characterizing the role of lncRNAs in development and disease. In this review, we discuss new findings implicating lncRNAs in controlling development of the central nervous system (CNS). The evolution of the higher vertebrate brain has been accompanied by an increase in the levels and complexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
120
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(121 citation statements)
references
References 219 publications
(368 reference statements)
1
120
0
Order By: Relevance
“…lncRNAs are RNAs . 200 nt that do not contain an open reading frame; although their biological meaning and function still need to be elucidated, ample evidence, including specific subcellular localization, tissue specificity, and association with disease, indicates that they may be essential regulators of cell function (27)(28)(29). The importance of lncRNAs in MS is highlighted by recent studies showing that various SNPs associated with MS in GWAS are located in genomic regions that code for lncRNAs (30) or regulate lncRNA expression in cis in human monocytes (31).…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs are RNAs . 200 nt that do not contain an open reading frame; although their biological meaning and function still need to be elucidated, ample evidence, including specific subcellular localization, tissue specificity, and association with disease, indicates that they may be essential regulators of cell function (27)(28)(29). The importance of lncRNAs in MS is highlighted by recent studies showing that various SNPs associated with MS in GWAS are located in genomic regions that code for lncRNAs (30) or regulate lncRNA expression in cis in human monocytes (31).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, intron-retaining transcripts have been attracting much attention as non-coding RNAs that play a physiological role (Wong et al 2013). In particular, many non-coding RNAs have been identified in human brain (Barry 2014;Clark and Blackshaw 2014). It is suggested that non-coding transcripts containing exon 1a or 41e play a physiological role in neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Other than housekeeping non-coding RNAs (ribosomal RNAs, transfer RNAs, and small nuclear RNAs), whose biological functions have been well defined, regulatory non-coding RNAs (siRNAs, microRNAs, and long non-coding RNAs) have recently shown to be actively involved in physiological regulations (Djebali, Davis et al 2012, Kornfeld andBruning 2014). Further, lncRNAs have been shown to perform transcriptional regulation through interaction with transcription factors in different tissues (Clark andBlackshaw 2014, Herriges, Swarr et al 2014). …”
Section: Car and Pxr Have Been Reported To Regulate Expression Of Spementioning
confidence: 99%